Integrating Anti-Corruption Values into English for Law: A Case Study of Constitutional Law Students at UIN Jurai Siwo Lampung - Sa’dulloh Muzammil (Diksi: Jurnal Pendidikan dan Literasi, 2026)
Anti-corruption education is a crucial preventive strategy amid the prevalence of corruption cases in Indonesia. Higher education institutions play a strategic role in instilling values of integrity in students, including through the English for Law course. This study focuses on students in the Constitutional Law (HTN) program at UIN Jurai Siwo Lampung to analyse their perceptions and needs regarding the integration of anti-corruption themes into English for Law instruction. The method used is a descriptive qualitative approach with data collection techniques involving classroom observation and semi-structured interviews with HTN students. The results indicate that HTN students are highly enthusiastic about integrating anti-corruption content into English language instruction due to its direct relevance to the study of state administration, oversight of power, and checks-and-balances mechanisms. They view this theme as highly relevant to their future academic and professional needs as prospective constitutional law experts, constitutional judges, legislators, or bureaucrats. The main challenges faced include limited knowledge of constitutional law vocabulary in English and a lack of understanding of international instruments such as the UNCAC. The study's recommendations include the development of contextual teaching materials highlighting corruption cases related to state administration, as well as interactive learning methods such as simulations of Constitutional Court hearings and role-playing exercises on legislative oversight